Development and Characterization of Chitosan and Chondroitin Sulfate Based Hydrogels Enriched with Garlic Extract for Potential Wound Healing/Skin Regeneration Applications - Fatima Masood; Muhammad Atif Makhdoom; Iftikhar Ahmed Channa; Sadaf Jamal Gilani; Ahmad Khan; Rabia Hussain; Syeda Ammara Batool; Kiran Konain; Saeed Ur Rahman; Abdul Wadood; May Nasser bin Jumah; Muhammad Atiq Ur Rehman (Gels, 2022)
Hydrogels can provide instant relief to pain and facilitate the fast recovery of wounds. Currently, the incorporation of medicinal herbs/plants in polymer matrix is being investigated due to their anti-bacterial and wound healing properties. Herein, we investigated the novel combination of chitosan (CS) and chondroitin sulfate (CHI) to synthesize hydrogels through freeze gelation process and enriched it with garlic (Gar) by soaking the hydrogels in garlic juice for faster wound healing and resistance to microbial growth at the wound surface. The synthesized hydrogels were characterized via Fourier-transform infrared spectroscopy (FTIR), which confirmed the presence of relevant functional groups. The scanning electron microscopy (SEM) images exhibited the porous structure of the hydrogels, which is useful for the sustained release of Gar from the hydrogels. The synthesized hydrogels showed significant inhibition zones against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). Furthermore, cell culture studies confirmed the cyto-compatibility of the synthesized hydrogels. Thus, the novel hydrogels presented in this study can offer an antibacterial effect during wound healing and promote tissue regeneration.